Second person reference in Indonesian Christian Prayer: a sociolinguistic analysis - André Wehrli; Norsimah Mat Awal (Penerbit UKM, 2014)
One might expect that the divine person addressed in prayers by Indonesian Christians matches those in biblical prayers. However, this seems not always to be the case. Since referential differences in such texts are not always obvious, the aim of this paper is to define steps for identifying who exactly is being addressed. For that purpose, sample prayers in Indonesian are analysed. These samples consist of prayers from an Indonesian Bible translation, Christian prayers in Indonesian books, and spontaneous prayers by Indonesian Christians, which were recorded and transcribed. The following steps were defined: 1) the grammatical analysis of nouns and pronouns, 2) the listing of relevant instances of referents, 3) the assignment of these instances to certain referents and 4) the comparison of the identified referents with the context of the analysed prayers. The findings show that the person addressed in Indonesian Christian prayers cannot reliably be identified without looking at the context. As for the recorded spontaneous prayers, the socio-religious background and a close look at the actual perception of the person praying are crucial for a reliable identification of the referent. This was done by comparing the results with interview responses of these persons. By applying the four mentioned steps, different addressees can be identified in prayers. In the examples of this analysis, the most significant difference was found between the addressee of prayers in the Bible compared to the addressee in spontaneous prayers. While 9 out of 11 Christians spontaneously address Jesus in their prayers, all investigated biblical prayers do not address Jesus. The findings show that the four steps applied are beneficial to a high degree, but in some circumstances, ambiguity may remain.